Cinema feito por mulheres: um estudo sobre a produção da imagem cinematográfica e a educação visual em Tão Longe é Aqui - Domingues, Ana Carolina (2019)
This work aims to study and understand the perception of womens filmmakers, and what the images produced by them tell us and educate us. For this, the work presents the feature film So Far is Here (2013) directed by Brazilian filmmaker and journalist Eliza Capai, whose story chronicles her trip to the African continent in 2010. The theoretical cut is based on authors who study and understand the image as responsible for a form of education, expression and control, for exercising an educational process over who sees them. The cognitive process that operates in the image, points to the theme of visuality, as a political exercise. So Far is Here "encroces" the cinematographic genres of road-movies, the documentary and the movie-letter, making it hybrid by the way it articulates in all these layers (genres). The methodology consists of decomposing and interpreting the “agent images” (ALMEIDA, 2009), as possible own documents to dialogue with the text. As a conclusion, we pointed out that So Far is Here belongs to the genre women's film, for addressing itself from another form of world perception that integrates women who share similar experiences. In this context of interpretation we chose the theme of motherhood to interpret the “agent images” produced and sequenced in the feature film.